The Theoretical and Practical Aspects of Entrepreneurship - Michałojć Joanna (My University, 2003)
The purpose of this paper is to take a closer look at entrepreneurship from different perspectives. Firstly, the aim is to analyze the meaning and definitions, describe stages of entrepreneurial venture and identify an entrepreneurial personality model. Secondly, the purpose is to examine issues that are crucial for every start-up: obtaining needed capital and understanding most prominent legal issues. To sum up, the first two chapters are intended to present the problem from the entrepreneur’s viewpoint. Furthermore, the intention is to transfer the meaning of entrepreneurship into the global perspective. Consequently, the next two chapters are projected to present the importance of new ventures for the economy, their current role and meaning. In addition, the policy towards SMEs is discussed in the light of possibilities given by free economy. Personally, I wanted to identify all prominent issues concerning entrepreneurship from local as well as global perspective: all problems that business creators confront as well as to review the value of entrepreneurship in the modern economy. Secondly, I wanted to evaluate the government policy towards small and medium enterprises in Poland. More specifically, I was trying to answer the question if it is easy to be an entrepreneur in Poland. In order to do that, I decided to analyze the business climate in Poland, whether it is favorable for investors. This problem is of the highest importance to me, a person who is just about graduating from a business school. I wanted to learn as much as possible about a process that many graduates may be involved in the nearest future. Finally, after understanding the importance of SME as well as identifying the government approach, I wanted to predict the path for future economic growth as well as the prospective position of entrepreneurial ventures. There have been many initiatives undertaken in order to encourage entrepreneurs to establish new businesses in Poland. However, the incentives are not the only factor taken into consideration by potential businessman. A business climate consisting of economy, financial situation, government, management, labor and marketing should be carefully examined. As long as Poland is rotted by corruption and overgrown beaurocracy, it will not fully take advantage of all opportunities created by free market.
Keywords: entrepreneurship; entrepreneur; business plan; economy; policy; climate business; Small and Medium Enterprises; Poland